HOW AND WHY DOES WORK MATTER? EMPLOYMENT CONDITIONS, ROUTINE ACTIVITIES, AND CRIME AMONG ADULT MALE OFFENDERS*. Issue 2 (21st February 2017) - APEL, ROBERT; HORNEY, JULIE
Abstract : An inverse relationship between employment and crime is well established, although the mechanisms that account for the correlation remain poorly understood. In the current study, we investigate the role of work quality, measured objectively (hours, income) as well as subjectively (commitment). A routine activities perspective is proposed for the work–crime relationship, and it inspires hypotheses about the way that work reduces crime indirectly, in part, through unstructured leisure and substance‐using behaviors that tend to carry situational inducements to offend. The results derive from within‐person analyses of monthly data provided by adult male offenders recently admitted to state prison in the Second Nebraska Inmate Study (N = 717 ; NT = 21, 965 ). The findings indicate that employment significantly reduces self‐report crime but only when employed men report strong commitment to their jobs, whereas other work characteristics are unrelated to crime. This indicates that, among serious criminally involved men, the subjective experience of work takes priority over its objective characteristics. The results also indicate that routine activities only partly mediate the relationship among work, job commitment, and crime, whereas the majority of the work–crime relationship remains unmediated.